Impact of inflammation on the osteoarthritic niche: implications for regenerative medicine. - Williams, E; Edwards, C; Cooper, C; Oreffo, R (2012)
Osteoarthritis (OA) is the most common form of arthritis worldwide and is the sixth leading cause of disability. It costs the UK economy approximately 1% of gross national product per annum. With an aging population, the cost of chronic conditions such as OA continues to rise. Historically, treatments for OA have been limited to painkillers, physiotherapy and joint injections. When these fail, patients are referred for joint replacement surgery. With the advent of tissue engineering strategies aimed at generating new bone and cartilage for repair of osteochondral defects, there has been considerable interest in exploiting these techniques to devise new treatments for OA. To date, little consideration has been given to the OA niche and attendant inflammatory milieu for any regenerative skeletal strategy. This review highlights the importance of understanding the osteoarthritic niche in order to modify existing tissue engineering and regenerative medicine strategies for the future treatment of OA.